Up and down the substantivization cline: response to Bekaert & Enghels. (May 2019) - Hartmann, Stefan
Abstract: In their target paper, Bekaert & Enghels (B&E) (2019) show convincingly that deverbal nominalizations differ with regard to their 'nouniness': while some capture the semantics of their base verbs quite faithfully, others approximate the semantic prototype of a noun as they refer to more concrete concepts. This is also reflected in their distributional behavior. This response paper relates B&E's considerations to a different word-formation pattern in another language and to diachrony. Drawing on a corpus study of German ung -nominalization, it is shown how intracategorial heterogeneity can evolve diachronically, and the implications of this study as well as the research presented in the target paper for our understanding of categorial shift are discussed. Highlights: Bekaert & Enghels show that deverbal nouns often show intracategorial heterogeneity. The present study taps into the diachronic origins of intracategorial heterogeneity. The relationship between categorial shift as a synchronic and a diachronic phenomenon is discussed.